2020
DOI: 10.1159/000505015
|View full text |Cite
|
Sign up to set email alerts
|

Apitherapy for Osteoarthritis: Perspectives from Basic Research

Abstract: Osteoarthritis is one of the most common rheumatic disease in the world and one of the leading causes of disability in the elderly. There is still no curative management for the disease, so the search for new therapeutic alternatives continues. Apitherapy is a therapeutic tool based on the use of beehive products used since ancient times and, at present, their mechanism of action begins to be known. Many of the mechanisms of action of the beehive products are useful for chronic articular pathophysiological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…Hence, future clinical studies of the effect of R. ponticum bee pollen on diseases associated with oxidative damage caused by ROS and RNS will be of interest. For example, it has been shown that bee pollen can alleviate the damage caused by ROS in the pathophysiological mechanism of joint oxidation in osteoarthritis [40]. Also, we found that P5–8 samples of R. ponticum bee pollen are effective on the microorganisms of S. aureus , L. monocytogenes , E. faecalis , E. coli , and P. aeruginosa .…”
Section: Discussionsupporting
confidence: 57%
“…Hence, future clinical studies of the effect of R. ponticum bee pollen on diseases associated with oxidative damage caused by ROS and RNS will be of interest. For example, it has been shown that bee pollen can alleviate the damage caused by ROS in the pathophysiological mechanism of joint oxidation in osteoarthritis [40]. Also, we found that P5–8 samples of R. ponticum bee pollen are effective on the microorganisms of S. aureus , L. monocytogenes , E. faecalis , E. coli , and P. aeruginosa .…”
Section: Discussionsupporting
confidence: 57%
“…Fresh royal jelly chemically contains water (60–70%), carbohydrates (11–23%), proteins (9–18%), lipids (4–8%), and other low compounds such as vitamins and minerals [ 16 ]. Studies exploring the active components of RJ have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The hirudotherapy has been shown to produce statistically significant improvement of arthritic conditions ( Cooper and Mologne, 2017 ) and has also been applied in cardiovascular diseases, reconstructive and microsurgery, cancer and metastasis, diabetes mellitus and its complications, infectious diseases, arthritis, and as analgesic ( Singh, 2010 ; Abdualkader et al., 2013 ). For an extensive review regarding these venom therapies, please see ( Mumcuoglu, 2014 ; Jagua-Gualdrón et al., 2020 ).…”
Section: Achievements With Animal Toxin-based Moleculesmentioning
confidence: 99%